Common Semantic Meanings of the Preposition (עַל/on) In Hebrew and Arabic (Journal of the College of Basic Education, 2022)
This study aims to clarify the importance of the comparative approach in linguistic studies and its application at one of the levels of the comparative linguistic lesson, which is the grammatical level in which we deal with one of the prepositions; This is due to its importance in formulating many linguistic structures and its main role in contextual linking.This study seeks to clarify the common grammatical functions and meanings of the preposition (on) in the Hebrew and Arabic languages, which reached (9) common functional meanings, namely: supremacy, accompaniment, transgression, reasoning or causation, circumstantial, agreement with ba, agreement with, hostility , agree to.